ANALYSIS OF THE RISK OF RECURRENT WHEEZING IN CHILDREN WITH BRONCHIOLITIS BASED ON THE WEIBULL MATHEMATICAL MODEL - Н. Токарчук; О. Очередько; А. Оверчук (Неонатологія, хірургія та перинатальна медицина, 2023)
Given the frequency of recurrent wheezing (up to 50 % of cases) in young children during the first year after bronchiolitis, the assessment of the prognostic value of diagnostic biological markers of bronchiolitis requires special attention. According to modern concepts, mast cells, eosinophils, play a significant role in the pathogenesis of bronchiolitis, with degranulation of which the release of cationic proteins (eosinophilic cationic protein (ECP), eosinophil-derived neurotoxin (EDN)) and molecular mediators, namely vascular cell adhesion molecule-1 (VCAM-1), which is a regulator of leukocyte adhesion and transendothelial migration. That is why VCAM-1, ECP and EDN are discussed as important prognostic markers in assessing the risk of recurrent wheezing in children with bronchiolitis. The aim of the study. To analyze the risk factors for recurrent wheezing in children with bronchiolitis, considering allergic history, the influence of external factors (passive smoking, place of residence), levels of VCAM-1, ECP, EDN in the blood serum. Material and Methods. This article is a part of the research work of the Department of Paediatrics No. 1 of Vinnytsia National Medical University named after M.I. Pyrohov on the topic "Optimization of diagnosis and treatment of somatic pathology in children", state registration No. 0115U007075. A clinical examination of 67 infants was carried out. The main group consisted of 34 children with bronchiolitis without a complicated allergic history. The comparison group consisted of 33 children with bronchiolitis who had a burdened allergic history. The average age of the children in the main group was 8.4±1.6 months, and 6.2±1.4 months in the comparison group. The analytical component of the study was based on parametric survival models (Weibull and generalized Gamma models). The analysis of Weibull models was performed in the statistical packages of analytical system R for Mac OS X FAQ, Version 3.1.0 2014-04-10, R. app 1.64 based on the Mac OS X 10.9 platform, 64-bit Intel Core i7 architecture. The study was approved by the Commission on Biomedical Ethics for compliance with the moral and legal rules for conducting medical research at Vinnytsia National Medical University named after M.I. Pyrohov. It was established that the research does not contradict the basic bioethical norms and meets the principles of compliance with the basic provisions of the GCP (1996), the Council of Europe Convention on Human Rights and Biomedicine (04.04.1997), WMA Declaration of Helsinki on Ethical Principles for Medical Research Involving Human Subjects (1964-2008) and Order of the Ministry of Health of Ukraine No. 690 of 23.09.2009 (as amended by Order of the Ministry of Health of Ukraine No. 523 of 12.07.2012). All patients were informed about the purpose and possible consequences of the research procedures. All patients signed an informed written consent to participate in the study prior to the procedure. Results of the study. The risks of recurrent wheezing in children with bronchiolitis according to the Weibull model were allergic history ( β=1,996) mixed feeding, and to an even greater extent artificial feeding ( β=7,832 and β=8,337). High serum levels of ECP β=5,03, EDN β=0,182 and VCAM-1 β=0,0254 are reliable markers of increased risk of recurrent wheezing in children with bronchiolitis. Living in rural areas ( β=-5,8) significantly reduces the risk of recurrent wheezing in children with bronchiolitis compared to children living in urban areas β=0.0162). Conclusions. 1. The levels of VCAM-1, ECP and EDN in the blood serum were recognized as reliable markers for the prognosis of recurrent vesicitis in children with bronchiolitis. The level of EDN ≤ 7 ng/ml in the blood serum is a prognostic marker for the risk of recurrent wheezing in children with bronchiolitis. 2. The hypothesis that artificial feeding in children with bronchiolitis with a complicated allergic history confirms and significantly increases the risk of recurrent vesicitis in children with bronchiolitis. The hypothesis about the role of passive smoking exposure in a significant increase in the risk of recurrent wheezing in children with bronchiolitis was confirmed only for patients with EDN levels not exceeding 7 ng/ml in the blood serum.